2023
DOI: 10.1001/jamanetworkopen.2023.15306
|View full text |Cite
|
Sign up to set email alerts
|

County-Level Maternal Vulnerability and Preterm Birth in the US

Abstract: ImportanceAppreciation for the effects of neighborhood conditions and community factors on perinatal health is increasing. However, community-level indices specific to maternal health and associations with preterm birth (PTB) have not been assessed.ObjectiveTo examine the association of the Maternal Vulnerability Index (MVI), a novel county-level index designed to quantify maternal vulnerability to adverse health outcomes, with PTB.Design, Setting, and ParticipantsThis retrospective cohort study used US Vital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Part of the differences they found might be explained by distinct proportions of these two vulnerability profiles that were not explored. Similarly, two recent studies from the US demonstrated strong associations between social vulnerability indices and PTB [25,26]. Both indices were based on geographical indicators of social vulnerability that blended several dimensions of social vulnerability together.…”
Section: Discussionmentioning
confidence: 94%
“…Part of the differences they found might be explained by distinct proportions of these two vulnerability profiles that were not explored. Similarly, two recent studies from the US demonstrated strong associations between social vulnerability indices and PTB [25,26]. Both indices were based on geographical indicators of social vulnerability that blended several dimensions of social vulnerability together.…”
Section: Discussionmentioning
confidence: 94%
“…Lower maternal education as a proxy for SES has been widely studied in this context, perceptions of neighborhood safety and the maternal vulnerability index, a composite measure that reflects physical, social, and health care needs, have also been associated with preterm birth, less use of prenatal care and poorer long-term outcomes. 219 , 220 While the mechanisms underlying these associations are not fully elucidated, these findings suggest that strategies improving social determinants of health for premature infants may have a positive effect on their long-term health and neurodevelopmental outcomes 221 and that, as such, advocacy by clinicians in this area is vital.…”
Section: Postnatal Managementmentioning
confidence: 99%
“…Rates of preterm birth have increased in the US in recent years, with an annual increase of 2% per year from 2014 to 2019, and considerable racial and ethnic disparities exist with the highest rate of preterm birth among non-Hispanic Black individuals . A variety of maternal factors, including socioeconomic status, access to health care, implicit bias, perceived discrimination, and environmental exposures have each been associated with risk of preterm birth . These upstream factors may partially account for the disproportionate burden of preterm birth experienced by racial and ethnic minoritized groups in the US .…”
Section: Introductionmentioning
confidence: 99%